Size Perusahaan Memoderasi Hubungan Good Corporate Governance, Green Supply Chain Management dan Green Accounting Terhadap Kinerja Keuangan Perusahaan - Topan Pamungkas; Iin Rosini; Suripto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine how company size influences the relationship between Good Corporate Governance, Green Supply Chain Management, and Green Accounting on Company Financial in Sri-Kehati index companies listed on the BEI from 2016 to 2022. This type of research is known as associative quantitative research . The population in this research is the Sri-Kehati index business actors listed on the Indonesia Stock Exchange between 2016 and 2022, totaling 25. The sampling approach is a saturated sampling technique. The sample for this research consists of 25 companies listed on the Indonesia Stock Exchange from 2016 to 2022, with 175 observation data obtained based on sample criteria. The data analysis method used is panel data regression analysis with Eviews-12.0. The findings of this study show that good corporate governance has a partial impact on company financial performance, while environmentally friendly supply chain management has a small impact and environmentally friendly accounting does not. The company size variable cannot moderate the influence of good corporate governance on the company's financial performance, the influence of green supply chain management on the company's financial performance, or the influence of green accounting on the company's financial performance.